2020
DOI: 10.1108/ijsi-01-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of 7075 Al alloy–SiC composites

Abstract: PurposeMechanical properties are highly sensitive to the microstructure, and these are indirectly related to solidification parameters and processing conditions. AA7075 possesses lightweight and excellent properties as structural material which can be optimized with SiCp addition and a good fabrication technique.Design/methodology/approach7000 series aluminium alloys exhibit the highest mechanical properties. They are used for high-strength structural applications such as aircraft parts and sporting goods. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A wide variety of ceramic particles like SiC, Al 2 O 3 , B 4 C, WC etc. have widely been used as reinforcing particles for aluminium (Rao and Rao, 2021;Bhushan, 2021). Al-Si alloys which are reinforced with SiC particles to manufacture metal matrix composites are used in cases where the elements are subjected to extreme wear conditions, particularly in the automobile and aircraft sector.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of ceramic particles like SiC, Al 2 O 3 , B 4 C, WC etc. have widely been used as reinforcing particles for aluminium (Rao and Rao, 2021;Bhushan, 2021). Al-Si alloys which are reinforced with SiC particles to manufacture metal matrix composites are used in cases where the elements are subjected to extreme wear conditions, particularly in the automobile and aircraft sector.…”
Section: Introductionmentioning
confidence: 99%
“…Gradually, ferrous metals have been replaced by aluminum alloys for manufacturing of automobile components (Lozano et al, 2009). Numerous studies were reported on the tribological properties of AMCs at ambient temperature (Bhushan, 2020;Soundararajan et al, 2020;Idusuyi and Olayinka, 2019;Kaushik and Singhal, 2018;Poria et al, 2016). In some cases, applications involving high temperatures like cylinder block and brake pad/disc are also studied at ambient temperature (Kumar et al, 2010;Lozano et al, 2009;Uyyuru et al, 2007).…”
Section: Introductionmentioning
confidence: 99%